PEMENUHAN HAK ATAS PEKERJAAN DAN PENGHIDUPAN YANG LAYAK BAGI PENYANDANG DISABILITAS DAKSA MELALUI PROGRAM REHABILITASI SOSIAL - Ismawati; Rima Vien Permata Hartanto; Triana Rejekiningsih (Jurnal PPKn, 2019)
This study aims to find out: 1) fulfillment of the right for occasions and decent live This study aims to find out: 1) fulfillment of the right for occasions and decent live for persons with physical disabilities through social rehabilitation program held by BBRSBD Prof. Dr. Soeharso; 2) the impacts of the social rehabilitation program on the fulfillment of the right for occasions and decent live for persons with physical disabilities held by BBRSBD Prof. Dr. Soeharso; 3) the barriers to social rehabilitation program in fulfilling the right for occasions and decent live for persons with physical disabilities held by BBRSBD Prof. Dr. Soeharso. This study uses qualitative research methods with purposive sampling and random sampling technique. Data collected by observation, interview and documentation. Checking the data validity by data triangulation and method triangulation. Interactive analysis model was used to analys the data. The results showed that: 1) The social rehabilitation program held by BBRSBD Prof. Dr. Soeharso to help fulfilling the right to work and a decent life for persons with physical disabilities are consist rehabilitation, resocialization, employment distribution and follow-up from the social rehabilitation program. 2) Impacts of the program: a) physiological impacts in the form of physical refunctionalization and giving of motion aids; b) the mental-social impact of growing independent, courageous, confident; c) intellectual impact in the form of increasing the ability to read, write and count and get the opportunity to improve the educational degree through the Kejar Paket program; c) the impact of vocationalism is the increase in work skills as a provision for work. 3) The barriers: a) Barriers from the persons with disabilities (Penerima Manfaat) are physical inability to support certain skills so that they are easy to give up, stubborn individuals who are difficult to adjust; b) Facilitator barriers are the quantity of facilitators and inadequate quality of facilitators due to lack of skills education background. c) barriers to facilities in the form of limited practice tools and hard road access. Full Paper